An evaluation of security features for preventing illegal distribution of digital content using quantitative methods - Muhammad Isma Farhan, Mohd Raza; Mazlina, Abdul Majid; Ajra, Husnul; Islam, Md. Shohidul; Aziman, Abdullah (IEEE, 2025)
In the current digital landscape, safeguarding digital content from unauthorized sharing is of paramount importance. This study concerns three key issues: the prevalent unauthorized sharing of content, user dissatisfaction with existing security measures, and the lack of alignment between expert opinions and user perceptions. This research addresses three critical problem statements. Firstly, it seeks to identify the current security features utilized to prevent the unauthorized distribution of digital content. Secondly, it aims to assess user perceptions of these features through a meticulously constructed survey; and lastly, the study endeavors to compare findings from a thorough literature review with user perceptions. Methodologically, this research encompasses an exhaustive literature review and a user perception survey to gain insights into effective security measures and recommendations for enhancement. The expected outcomes include a more profound understanding of the effectiveness of current security measures and suggestions for enhancing digital content protection. Through this study, it has been emphasized the significance of digital content security and put forward collaborative avenues for improvement.